PEEK Cages versus PMMA Spacers in Anterior Cervical Discectomy: Comparison of Fusion, Subsidence, Sagittal Alignment, and Clinical Outcome with a Minimum 1-Year Follow-Up - Jan-Helge Klingler; Marie T. Krüger; Ronen Sircar; Evangelos Kogias; Christoph Scholz; Florian Volz; Christian Scheiwe; Ulrich Hubbe (The Scientific World Journal)
Purpose. To compare radiographic and clinical outcomes after anterior cervical discectomy in patients with cervical degenerative disc disease using PEEK cages or PMMA spacers with a minimum 1-year follow-up. Methods. Anterior cervical discectomy was performed in 107 patients in one or two levels using empty PEEK cages (51 levels), Sulcem PMMA spacers (49 levels) or Palacos PMMA spacers (41 levels) between January, 2005 and February, 2009. Bony fusion, subsidence, and sagittal alignment were retrospectively assessed in CT scans and radiographs at follow-up. Clinical outcome was measured using the VAS, NDI, and SF-36. Results. Bony fusion was assessed in 65% (PEEK cage), 57% (Sulcem), and 46% (Palacos) after a mean follow-up of 2.5 years. Mean subsidence was 2.3–2.6 mm without significant differences between the groups. The most pronounced loss of lordosis was found in PEEK cages (−4.1°). VAS was 3.1 (PEEK cage), 3.6 (Sulcem), and 2.7 (Palacos) without significant differences. Functional outcome in the PEEK cage and Palacos group was superior to the Sulcem group. Conclusions. The substitute groups showed differing fusion rates. Clinical outcome, however, appears to be generally not correlated with fusion status or subsidence. We could not specify a superior disc substitute for anterior cervical discectomy. This trial is registered with DRKS00003591.